2023
DOI: 10.1186/s13550-023-01005-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of novel macrocyclic chelates on the targeting properties of the 68Ga-labeled Gastrin releasing peptide receptor antagonist RM2

Abstract: Background The gastrin-releasing peptide receptor (GRPr) is a molecular target for the visualization of prostate cancer. Bombesin (BN) analogs are short peptides with a high affinity for GRPr. RM2 is a bombesin-based antagonist. It has been demonstrated that RM2 have superior in vivo biodistribution and targeting properties than high-affinity receptor agonists. This study developed new RM2-like antagonists by introducing the novel bifunctional chelators AAZTA5 and DATA5m to RM2. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…There are two studies reporting the biodistribution of [ 68 Ga]Ga-DOTA-RM2 in mice bearing PC-3 xenografts. , Corresponding data for 1 h p.i. are listed in Table .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are two studies reporting the biodistribution of [ 68 Ga]Ga-DOTA-RM2 in mice bearing PC-3 xenografts. , Corresponding data for 1 h p.i. are listed in Table .…”
Section: Resultsmentioning
confidence: 99%
“…In this respect, the influence of the metal chelator has also been investigated recently for the GRPr. 30 In this study, antagonistic peptide JMV594 was coupled via the 4-amino-1carboxymethyl-piperidine spacer to the chelators AAZTA 5 and DATA 5m to prepare conjugates DATA 5m -RM2 and AAZTA 5 -RM2, respectively. Comparative biodistribution studies with the 68 Ga-labeled compounds, including DOTA-RM2, revealed the influence of the corresponding chelators on the pharmacokinetics and targeting properties.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a head-to-head comparison with 68 Ga-RM2, 68 Ga-LF1 showed a comparable tumor uptake ( 68 Ga-RM2, 6.51% ± 1.10%ID/g; 68 Ga-LF1, 6.34% ± 0.81%ID/g at 1 h pi) with nearly 1/3 uptake values of the pancreas and a higher tumor-tobackground ratio (including liver, kidney, muscle, blood, and bone) at all time points in biodistribution study. 80 Another well-behaved Sta 13 BBN(6−14)-based radiopharmaceutical, the hydrophilic 68 Ga-118 ( 68 Ga-RM26) with a (PEG) 2 linker, displayed high tumor uptake (8.1% ± 0.4%ID/g at 1 h pi) and fast clearance rate of off-tumor binding (at 1 h pi, small intestine, 1.4% ± 0.5%ID/g, and pancreas, 5.7% ± 0.8%ID/g; at 3 h pi, small intestine, 0.27% ± 0.05%ID/g, and pancreas, 0.6% ± 0.2%ID/g) in PC-3 tumor-bearing mice model. 64,81 Additionally, 68 Ga-RM26 in healthy volunteers showed high absorbed doses in the urinary bladder wall (1.09 mSv/MBq) due to renal excretion mode followed by the pancreas (0.23 mSv/MBq).…”
Section: Grpr Antagonist-based Radiopharmaceuticalsmentioning
confidence: 99%